Evaluation of the efficacy of Aframomum melegueta and Piper guineense for controlling Callosobruchus maculatus in Vigna unguiculata (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluates the insecticidal effects of two plant powders, Piper guineense and Aframomum melegueta, on the mortality and emergence of Callosobruchus maculatus, a significant pest of stored beans. Using a completely randomized design (CRD), different concentrations (0 g, 5 g, 10 g, 15 g, and 20 g) of the plant powders were applied to 100 g samples of black-eyed peas. Mortality rates were recorded daily for seven days. Data collected was subjected to descriptive statistics and analysis of variance. Piper guineense exhibited a remarkable insecticidal effect, achieving 100% mortality across all concentrations by Day 6. In contrast, Aframomum melegueta showed a more gradual effect, with the highest concentration (20 g) reaching only 93.33% mortality by Day 7. Additionally, P. guineense completely suppressed the emergence of adult weevils at 5 g and 15 g concentrations, while A. melegueta achieved only moderate suppression at higher concentrations. Piper guineense recorded higher average mortality at 15 g (73.33%) and 20 g (67.62%) compared to A. melegueta (57.14% and 56.67%, respectively), though these differences were not statistically significant (p > 0.05). Notably, P. guineense completely suppressed adult weevil emergence at some concentrations, highlighting its practical potential as a natural insecticide for managing C. maculatus in stored beans and supporting its use in sustainable pest control strategies.
Keywords: Concentrations; Emergence; Insecticidal; Mortality